DESAIN WEBSITE E-COMMERCE BATIK KENANGA SUKOHARJO - Safitri Nurjannah; Evelyne Henny Lukitasari; Ahmad Khoirul Anwar (Canthing, 2024)
Indonesia is known as a country that has many cultural variations. As time and technology progress, the spread of batik leads to commercial development, but the more people who buy and sell, the less benefits are created by each business actor, therefore creativity is needed to support economic progress in every sale and one of them is using online-based promotional media such as E-Commerce with a website as a distribution bridge. The solutions offered are marketed through supporting websites. Batik Kenanga is a type of production service in solid form, Batik Kenanga prioritizes quality, but the problem that occurs is that the growth of batik is starting to grow rapidly around it, and requires online introduction, so that it can be accessed by the wider community. . The aim of this final assignment is to expedite the sales process and become a promotional medium. Kenanga Batik sales use qualitative design methods which are then further developed into new, more attractive promotions and are supported by several wider publication media, so that the products offered are widely known. Keywords: Design, Website , E-Commerce, Kenanga Batik